2010
DOI: 10.5194/aab-53-708-2010
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins C and E affect plasma metabolites and production performance of layer chickens (<i>Gallus gallus domesticus</i>) under condition of high ambient temperature and humidity

Abstract: Abstract. This study was carried out to investigate the effects of vitamins C and E on some plasma metabolites and production performance of layer chickens reared under hot tropical climate. 720 White Leghorn (L33) layer chickens and 39 weeks old were divided into four groups of 180 birds. One group was fed with basal diet (control) and treatment groups were fed with basal diet supplemented with 150 mg of vitamin C/kg of diet, 150 mg of vitamin E/kg of diet, while the last group was supplemented with 150 mg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…However, similar results were also obtained by a combination of vitamin E at 800 mg/kg level and C at 1000 mg/kg level. In agreement with our findings, several studies have reported increased egg production when Japanese quails fed diets supplemented with vitamin E and/or C (Bardakcioglu et al 2005;Sahin et al 2006;Ajakaiye et al 2010;Caurez and Olo 2013;Abedi et al 2017). In the current study, although the dietary addition of vitamin E plus C raised the total weight of produced eggs, no treatment effect was observed on the average egg weight in disagreement with Ipek and Dikmen (2014).…”
Section: Egg Production Traitssupporting
confidence: 93%
See 1 more Smart Citation
“…However, similar results were also obtained by a combination of vitamin E at 800 mg/kg level and C at 1000 mg/kg level. In agreement with our findings, several studies have reported increased egg production when Japanese quails fed diets supplemented with vitamin E and/or C (Bardakcioglu et al 2005;Sahin et al 2006;Ajakaiye et al 2010;Caurez and Olo 2013;Abedi et al 2017). In the current study, although the dietary addition of vitamin E plus C raised the total weight of produced eggs, no treatment effect was observed on the average egg weight in disagreement with Ipek and Dikmen (2014).…”
Section: Egg Production Traitssupporting
confidence: 93%
“…Vitamin E and vitamin C play a major role as antioxidants in biological systems and act individually or synergistically such that vitamin E explicates its antioxidant function in lipid phases whereas vitamin C in aqueous compartments by reacting with peroxyl radicals and by restoring the antioxidant properties of vitamin E (Cotelle et al 2003). Studies on poultry have reported that dietary supplementation with vitamins E and C, alone or together, can improve growth performance (Sahin and Kucuk 2001;Ajakaiye et al 2010), egg production and egg quality (Ajakaiye et al 2011;Caurez and Olo 2013). Because the most of studies were conducted under heat stress condition, further research is necessary to study the effects of additional vitamin E and C in diet of quails reared under standard environmental condition.…”
Section: Introductionmentioning
confidence: 99%
“…Its determination is indicative of oxidative stress in the liver tissue, since a high concentration of the enzymes is linked to the liver disease (Perić et al, 2010). In the study of Ajakaiye et al (2010) and Jiang et al (2013), the level of AST and ALT did not differ between the control and the vitamin E treated birds up to the levels of 150 mg/kg and 200 mg/kg, respectively, which may be due to the difference in experimental protocol, dose, and duration of vitamin E. Similar results were reported by Perić et al (2010) when broiler chicks were supplemented with 0.3 ppm selenium. In this study, reduced concentration of liver enzymes may be due to the antioxidative effect of vitamin E.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there was a beneficial effect of vitamin C supplementation in the diet of broilers on body weight, of broilers. Studies on poultry have reported that dietary supplementation with vitamins C, alone, can improve growth performance (Sahin and Kucuk 2001;Ajakaiye et al 2010) On the other hand, results of Ipek et al( 2007) mentioned that the highest body weight was demonstrated in quail on 500 mg of Vitamin C/kg feed and Durrani et al (2008) found when giving Aloe extract 10 ml/liter to broilers in drinking water resulted in better body weight. Vathana et al (2002) reported that during the first three weeks, no difference in body weight among different treatments was detected (p>0.05).…”
Section: Body Weight (Bw)mentioning
confidence: 99%
“…Vitamin C with other vitamins such as vitamin E play a major role as antioxidants in biological systems and act individually or synergistically such that vitamin E explicates its antioxidant function in lipid phases whereas vitamin C in aqueous compartments by reacting with peroxyl radicals and by restoring the antioxidant properties of vitamin E (Cotelle et al, 2003). Studies on poultry have reported that dietary supplementation with vitamin C, alone can improve growth performance (Sahin and Kucuk 2001;Ajakaiye et al 2010). Al-Ghamdi (2008) suggested that the alteration in plasma vitamin C level can be used as a heat stress indicator in broiler chickens.…”
mentioning
confidence: 99%